2008
DOI: 10.1002/ajim.20629
|View full text |Cite
|
Sign up to set email alerts
|

Shift‐work and suicide ideation among police officers

Abstract: Prevalence of suicide ideation significantly increased among policewomen with higher depressive symptoms and increasing day shift hours, and among policemen with higher PTSD symptoms with increasing afternoon shift hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 43 publications
(41 reference statements)
1
68
0
6
Order By: Relevance
“…However, this corresponds with a recent study carried out within a Norwegian police force (Berg et al, 2006;Berg, Hem, Lau, Haseth, & Ekeberg, 2005). Lastly, shift work was assessed by means of self-report, whereas other studies have used objective measures from the payroll records of police officers allowing to observe changes in shift work spanning the last few year of the officers' police career (Violanti et al, 2008). Future research should include longitudinal data, compare the effects of different shift-rosters over time, and include more objective measures of sleep, stress and health.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, this corresponds with a recent study carried out within a Norwegian police force (Berg et al, 2006;Berg, Hem, Lau, Haseth, & Ekeberg, 2005). Lastly, shift work was assessed by means of self-report, whereas other studies have used objective measures from the payroll records of police officers allowing to observe changes in shift work spanning the last few year of the officers' police career (Violanti et al, 2008). Future research should include longitudinal data, compare the effects of different shift-rosters over time, and include more objective measures of sleep, stress and health.…”
Section: Discussionmentioning
confidence: 95%
“…This can lead to a disruption of circadian rhythm, which in turn can cause internal de-synchronization and subsequent psychological and physiological disturbances (Violanti et al, 2008). Although prior studies have commonly shown that shift work is negatively associated with sleep (Akerstedt, 2003;Knutsson, 2003;Peacock, Glube, Miller, & Clune, 1983;Phillips et al, 1991;Vila, 2006), differences between shift and non-shift workers could not be detected in all investigations (Neylan et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is noteworthy that long WHs and shift work remained as significant associates with suicidal ideation after controlling possible confounders. Although long WHs more than 60 hours per week were well identified as a risk factor for suicidal ideation and other mental illnesses, as well, in prior research 11,12,21,22) , the association of shift work with suicidal ideation was identified in specific jobs such as police officers only 23) . Because the 2008 CHS was implemented nationwide, our analysis elucidated how shift work linked with suicidal ideation in all occupations.…”
Section: Discussionmentioning
confidence: 99%